(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-2-10-22 A number of points of view on the problem of demarcation of the statuses of language systems, as well as some concepts based on the structural principle of distinguishing idioms in Russian and foreign linguistics, related to the concept of “regional” language”, are considered, for example, ‘sister languages’, ‘collateral languages’ and the conception of ‘Slavic literary microlanguages’ by A. Dulichenko. The author asserts that there are two main principles in contemporary linguistics for determining an idiom as ‘language’ or ‘dialect’: functional and structural. Functional approach implies the description of a language as a medium of communication within a language community, and appropriation of the volume of functions that a language covers to the current level of development of society. And the structural one focuses on its genetic relationships and a number of lexicostatistical methods, such as using of Swadesh-list and valuation of mutual intelligibility. In this regard, it is especially noted that none of the listed approaches can be considered absolute and both of them should be implemented in a complementary way with detailed examination of current sociopolitical practices in language community in particular. On the basis of the proposed approaches and the analysis of the linguistic situations of a number of European regions and sociolinguistic peculiarities of some regional and minority languages of Europe and Slavic microlanguages, the most important distinctive features of regional languages are described. Key words: regional language, minority language, dialect, Slavic literary microlanguages, language situation, language policy, diglossia